2002
DOI: 10.1111/1468-0432.00155
|View full text |Cite
|
Sign up to set email alerts
|

Reflexive Fathers: Negotiating Parental Leave and Working Life

Abstract: The emergence of parental leave schemes has been the most important area of expansion for the Norwegian welfare state in the 1990s. Schemes have been extended, and special rights have been granted to fathers. The main underpinning of this strategy is the intention to bolster the fathers' contact with and care for their children. Another objective is to share the benefits and burdens of working life and family life between men and women. In this article we analyse how fathers construct different fatherhood prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
23

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 3 publications
(3 reference statements)
3
105
0
23
Order By: Relevance
“…The most common activity carried out by fathers is playing with their children. The high percentage is not surprising as there have been previous studies, such as that by Brandth and Kvande (2002), that found that the activity fathers were most involved in was playing with their children. Lastly, it should be mentioned that all the tasks are shared at least equally to a larger degree by fathers who used paternity leave, with the exception of taking children to and from preschool or school.…”
Section: Dependent Variables: the Division Of Reproductive Tasksmentioning
confidence: 69%
“…The most common activity carried out by fathers is playing with their children. The high percentage is not surprising as there have been previous studies, such as that by Brandth and Kvande (2002), that found that the activity fathers were most involved in was playing with their children. Lastly, it should be mentioned that all the tasks are shared at least equally to a larger degree by fathers who used paternity leave, with the exception of taking children to and from preschool or school.…”
Section: Dependent Variables: the Division Of Reproductive Tasksmentioning
confidence: 69%
“…Their efforts have received increasing policy support at both the national and European levels (Hobson 2002;Moss 2014). However, the company level, especially employers' and co-workers' attitude towards active fathers, is likely to be of particular importance for the transformation of the male gender role (Brandt and Kvande 2002;Haas and Hwang 2009;Behnke and Meuser 2012). Moreover, mothers need to accept fathers as their equals when it comes to parental care for children in order for the new male role to become established (Allen and Hawkins 1999).…”
Section: Changing Gender Rolesmentioning
confidence: 99%
“…According to this scale, responses follow a ranking which varies from zero (0) to four (4), expressing opinions between two extremes: not demanding or without influence (0) and very demanding or very great influence (4). The remaining scale variations reflect the following levels: almost not demanding or low influence (1), slightly demanding or average influence (2) and somewhat demanding or great influence (3).…”
Section: Anmentioning
confidence: 99%
“…Studies show parents' longer length of time in the work environment (4) ; their exposure to stressful situations, caused by work conflicts (5) ; and the development of certain activities -for example, work shifts (6) -as practices that reduce time spent with children.…”
Section: Introductionmentioning
confidence: 99%